2017
DOI: 10.1038/s41598-017-10115-5
|View full text |Cite
|
Sign up to set email alerts
|

Multipoint Tissue Circulation Monitoring with a Flexible Optical Probe

Abstract: Compromised circulation is a potential complication during the postoperative period following tissue transplantation. The use of a monitoring device allows physicians to detect compromised circulation immediately. Such monitoring devices need to be continuously usable, wearable, and area-detectable. However, existing devices fail to satisfy all of these requirements simultaneously. We developed a wearable, multipoint pulse wave-monitoring device. An array of reflective optical sensors implemented on a thin fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The results create new possibilities for studying a broad range of O 2 -mediated physiological and pathological processes in animal models, with potential for human translation. Examples include investigating function in specific regions of the brain using localized O 2 changes as surrogates of neural activity (32,(42)(43)(44), targeting of tumors via their association with hypoxia environments and low rStO 2 (3,45), and postoperative (multisite) monitoring of tissue transplantation (e.g., flap reconstruction) where the early detection of compromised circulation in the form of low rStO 2 is critical (46,47). For instance, these oximetry implants, either in the free-standing formats or mounted on conventional biopsy needles, can guide tumor targeting in specific regions by providing locationsensitive rStO 2 values in real time.…”
Section: Discussionmentioning
confidence: 99%
“…The results create new possibilities for studying a broad range of O 2 -mediated physiological and pathological processes in animal models, with potential for human translation. Examples include investigating function in specific regions of the brain using localized O 2 changes as surrogates of neural activity (32,(42)(43)(44), targeting of tumors via their association with hypoxia environments and low rStO 2 (3,45), and postoperative (multisite) monitoring of tissue transplantation (e.g., flap reconstruction) where the early detection of compromised circulation in the form of low rStO 2 is critical (46,47). For instance, these oximetry implants, either in the free-standing formats or mounted on conventional biopsy needles, can guide tumor targeting in specific regions by providing locationsensitive rStO 2 values in real time.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical reports showed that temperature change occurs in some cases after compromised circulation but not in all cases, suggesting that the results of our animal model are consistent with the findings of previous clinical studies. Thus, by combining colour and temperature measurement with other existing wearable methods, such as photoplethysmography sensors 17 , compromised circulation cases can be picked up with higher sensitivity, thereby improving the reliability of the detecting system. Furthermore, temperature is expected to provide supporting information to evaluate the progression of compromised circulation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we measured acute changes instead of the conventional chronic changes in compromised circulation using wearable sensors. Our wearable monitoring system has potential to improve the user experience for both patient and medical workers, but requires compact sensors 17,34 . Conventional methods using spectrometry measure optical reflection more precisely by scanning multiple wavelengths.…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive judgment as device output www.nature.com/scientificreports/ elements assembled on a thin, flexible substrate based on our previous studies [49][50][51][52][53][54] . In addition to its flexibility, its durability and biological safety were designed and verified for one-week use 54 .…”
Section: Staff Findings Normal Follow-up Required Abnormal Totalmentioning
confidence: 99%
“…We utilised our experience of ultra-flexible, thin electronic sensor arrays to design a wearable sensor durable enough for clinical application 49 52 . We have previously reported the utility and accuracy of the sensor in animal models and a healthy subject model 53 , 54 . By applying algorithmic analysis to assess the multi-modal data, we were able to reproduce the decisions of clinical surgeons using the sensor-based assessment 55 .…”
Section: Introductionmentioning
confidence: 99%